SACRIFICE: CORE OF VEDIC RELIGION AND CHRISTIANITY - Malieckal, Louis (Journal of Dharma, 1989)
Sacrifice is indeed a universal phenomenon both in the secular as well as religious sense. Every religion has some form of cult, ritual action or sacrifice so much so that, according to Van de Lieuw, "the idea of sacrifice is inseparable from any form of religion."1 We also speak about sacrifices in life, e.g. about some body who sacrifices his time, energy, comfort, money etc. for the sake of his fellowmen; about some one who makes sacrifice for the sake of truth, honesty, justice, freedom, fellow-feeling etc. Thus there is a generality of human experience, ritual and actual, of sacrifice. But it appears next to impossible to determine and define what exactly sacrifice is or means. Victor Warnach has therefore rightly said: "Sacrifice is a complex multi-faceted phenomenon embracing a variety of forms such that any attempt to define it in terms of univocal categories will be tantamount to a criminal act."2 While we are fully aware of this fact about the concept of sacrifice, in the present study we are trying to cast a glance at it relating it to Vedic Hinduism and Early Christianity. And we hope to derive some benefit from it for our religious and liturgical praxis and actual life today.